Faktor-Faktor yang Mempengaruhi Kinerja Sistem Informasi Akuntansi di LPD: Studi Kasus di Kecamatan Tabanan - Dewi, Ni Putu Shinta; Sudiartana, I Made; Cahyani, Ni Putu Putri (Jurnal Inovasi Akuntansi (JIA), 2025)
This study aims to obtain empirical evidence regarding the influence of user involvement, personal technical ability, top management support, development formalization, and user training and education on the performance of Accounting Information Systems (AIS) at Village Credit Institutions (LPDs) in Tabanan District. The research employed a purposive sampling method with 59 respondents from LPDs in Tabanan Regency. Multiple linear regression analysis was utilized as the data analysis technique to examine the relationships between the independent variables and AIS performance. The research findings demonstrated that user involvement, personal technical ability, top management support, development formalization, and user training and education all have a positive effect on AIS performance. These results imply that AIS performance at LPDs can be effectively improved through comprehensive strategies that focus on enhancing user involvement, developing technical competencies, strengthening managerial commitment, formalizing system development processes, and investing in user training programs.